EL FOTOLIBRO EN ESPAÑA EN LOS COMIENZOS DEL SIGLO XXI: DE LA AMENAZA DIGITAL A LA APRECIACIÓN GENERALIZADA - Mtr. Juan GIL SEGOVIA (Fonseca, Journal of Communication, 2023)
The current situation of the photobook, both in Spain and in other countries, is very strong. This is due to the fact that there has been an unprecedented expansion of this format. While it is true that publications have always been an appreciated vehicle for putting the photography into circulation, the digital technology seemed to threaten traditional media, deriving the photograph to virtual forms of production and dissemination.